Between Desire and Hope: Ethnic Relations and the Notion of Bangsa Malaysia in Gadoh - Mahyuddin Ahmad (Kajian Malaysia, 2011)
The objective of this paper is to examine the representation of ethnic relations in Gadoh (fighting), a film jointly directed by two activist filmmakers in Malaysia. Essentially, this film revisits the idea of Bangsa Malaysia, rendering this notion as something that is attainable; indeed, as evidenced from the narrative, the film presents the hope for equal ethnic relations in Malaysia as not just a figment of one's imagination but also an achievable goal. However, problems arise when the hope for Bangsa Malaysia is adopted unquestionably by the narrative of Gadoh. In this regard, this paper argues that while it is crucial to have hope for ethnic equality, and to sow this idea in the minds of the youth of the country, the film's narrative ignores the prickly reality that racism is not simply a discourse. It is an ideology that confronts Malaysians from all walks of life, and to eradicate racism requires a wholesale structural change in the larger context of society. Given the increasingly authoritative political culture in Malaysia, this is a tall order for a film.